The "lived life´s spectacle" and the history as it becomes - Barbosa, Marialva (2021)
This essay aims to reflect on the daily life entangled in the affectations of the present, from the articulation between the daily life as a lived spectacle and history in the dimension of what could have been and not as what happened in the past. It is a story of the probable in which the dimension of lived life allows the articulation of other paths of possibilities.